Burden of cytomegalovirus DNAemia among pediatric renal transplant patients on antiviral prophylaxis: A hospital‐based analysis. (31st December 2019) - Mehta, Kayur; Al‐Yabes, Ohoud; Allen, Andrew; Williams, Angela; Petrich, Astrid; Langlois, Valerie; Hébert, Diane; Allen, Upton
Abstract: Introduction: We examined the burden of CMV DNAemia and time to such events among renal transplant patients receiving CMV prophylaxis. We targeted the first year after transplantation, with the primary focus being on the first 3 months. Methods: We conducted a retrospective review of renal transplant patients (<18 years) who were transplanted and followed at our center between January 2007, and December 2017. Clinical and laboratory data were obtained from the medical records and laboratory databases. Results: Among 141 patients, the median age at transplant was 12.7 years (range 0.87‐17.83 years). CMV DNAemia was detected in 33 of 77 patients eligible for prophylaxis (42.9%; 95% CI 31.6‐54.6) during the first post‐transplant year. Proportionately more D+R− patients were present among patients with DNAemia compared with those without DNAemia (15/38, 39.5% vs 16/103, 15.5%, P  = .005). Median time to first positivity was 134 days (range 0‐304 days). Eight patients had a positive PCR during the first 3 months (5.7% of all patients). Among those eligible for prophylaxis, 6.5% had DNAemia during the first 3 months while on prophylaxis. Among patients whose first positive PCR was after 3 months post‐transplant, the median time to positivity was 52 days (range 13‐214 days) after the end of prophylaxis. Conclusions: Breakthrough CMV DNAemia was documented among children receiving antiviral prophylaxis. While routine monitoring while on prophylaxis might not be warranted for the majority of patients, studies are needed to determine the optimal indications for CMV PCR testing while on prophylaxis.